Before Einstein The Fourth Dimension in Fin-de-Siècle in Literature and Culture - L. Throesch, Elizabeth (Anthem Nineteenth-Century Series, 2017)
Before Albert Einstein proposed the concept of four-dimensional spacetime, late Victorian scientists, radical philosophers and writers were discussing the possibility of a different kind of fourth dimension. Before Einstein offers the first book-length examination of the impact of pre-Relativity four-dimensional theory on literature and culture at the turn of the twentieth century.